The Effect Of Mingle Night Habituation On Improving Students’ Speaking Skills At Bestone Education English Course - Putri Hariza Sholihah; Lasmini Lasmini; Opani Mutiatul Barriyah; Mira Ilya Maisaroh; Selamet Riadi Jaelani (Jurnal Riset Rumpun Ilmu Bahasa, 2023)
The objective of this study is to find out how the effect of habituation of Mingle Night program in improving students' English speaking ability at BestOne Education English Course. The method used in this research is descriptive qualitative research design. The data collection methods used were observation, interview, and documentation. The participants in this study amounted to 15 students at the BesOne Education course. The results of this study show that the impact of the Mingle Night program can increase students' vocabulary and improve students' English speaking skills. In addition, the Mingle Night program can also increase self-confidence and build mental in speaking in front of many people. This Mingle Night program is also different from other programs that students have encountered because in Mingle Night students can be free in speaking and having opinions without fear of the wrong word structure. In conclusion, the Mingle Night program at BestOne Education is considered effective in improving students' speaking skills. In addition, tutor assistance and support also greatly affect the effectiveness of this Mingle Night program.